INVESTIGATION OF THE MURABAHAH FINANCING AGREEMENT FOR FORCE MAJEURE DEBTORS - Mayangsari, Erika; Rini, Wavia Silvi Dhesinta (SYNTIFIC, 2025)
Background. Islamic banking in Indonesia is a manifestation of the fulfillment of the expectations of people who need an alternative banking system and also meet the principles of Sharia. This research examines the handling of murabahah financing due to debtors experiencing force majeure in Islamic banks, in accordance with applicable legal corridors. Research method. There is a type of research that is included in the type of normative research. The approach used is the legislative approach, the conceptual approach, and the comparative approach. Findings. The handling of problematic murabahah funding resulting from a force majeure event on the part of the customer has two handling efforts, namely rescue efforts and efforts to resolve problematic murabahah financing. The obstacles in handling problematic murabaha financing caused by force majeure are both external consumer variables and internal bank factors. Conclusion. It is reasonable to assume that Islamic banks will maximize risk management and the concept of prudence in their business operations to reduce the impact of the existence of problematic murabaha financing brought on by force majeure.